Special aspects of healing wounds after tooth extraction in patients with diabetes mellitus: Special aspects of healing wounds after tooth extraction in patients with diabetes mellitus - Barylo, О.; Kanishyna, Т. (Actual Dentistry, 2018)
The purpose: of our study was to investigate how the introduction of PRF into a postoperative wound affects the course of its healing after tooth extraction in patients with diabetes. Materials and methods. The study involved 20 patients with Type 2 diabetes mellitus, treated in the maxillofacial department of Vinnitsa Regional Pirogov Clinical Hospital. Histological preparations were immediately prepared from a small part of the fibrinous convolution. The sections of the fibrin convex preparation were made and stained with fibrin: orange-reddish-blue on Zerbino D.D., Lukasevich L.L. (modified method of Martius-Scarlet-Blue), and also stained with hematoxylin-eosin. Results. Histological examination of the fibrin convex colored with hematoxylin-eosin showed that it consists of filaments of fibrin and a large number of platelets. Conclusions. The use of platelet-rich fibrin (Platelet Rich Fibrin, PRF) after tooth extraction in patients with diabetes mellitus promotes faster regeneration of the post-extraction well. This can be explained by the fact that thrombocytory growth factors stimulate angiogenesis, and fibrin stimulates proliferation of fibroblasts. Clinical observations of a mild postoperative period in PRF patients coincided with the OHIP-14 survey data. Key words: diabetes mellitus, regeneration, Platelet Rich Fibrin, alveolar socket.